2022
DOI: 10.1086/717679
|View full text |Cite
|
Sign up to set email alerts
|

Do Interactions among Microbial Symbionts Cause Selection for Greater Pathogen Virulence?

Abstract: The ecological and evolutionary consequences of microbiome treatments aimed to protect plants and animals against infectious disease are not well understood, even as such biological control measures become more common in agriculture and medicine. Notably, we lack information on the impacts of symbionts on pathogen fitness with which to project the consequences of competition for the evolution of virulence. To address this gap, we estimated fitness consequences for a common plant pathogen, Ustilago maydis, over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 86 publications
(112 reference statements)
1
5
0
Order By: Relevance
“…May et al 2022). May et al (2022) have shown that when a plant host (Zea mays) is infected by a pathogenic fungus (Ustilago maydis), parasite fitness is maximised at higher levels of virulence in the presence of a defensive symbiont (Fusarium verticillioides), in agreement with our model. However, experimentally coevolved pathogenic Staphylococcus aureus and protective Enterococcus faecalis in Caenorhabditis elegans hosts, which led to a reduction in pathogen virulence; the same study system has also been shown to generate fluctuating selection dynamics in pathogen virulence and host protection (Ford et al 2017).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…May et al 2022). May et al (2022) have shown that when a plant host (Zea mays) is infected by a pathogenic fungus (Ustilago maydis), parasite fitness is maximised at higher levels of virulence in the presence of a defensive symbiont (Fusarium verticillioides), in agreement with our model. However, experimentally coevolved pathogenic Staphylococcus aureus and protective Enterococcus faecalis in Caenorhabditis elegans hosts, which led to a reduction in pathogen virulence; the same study system has also been shown to generate fluctuating selection dynamics in pathogen virulence and host protection (Ford et al 2017).…”
Section: Discussionsupporting
confidence: 88%
“…To date, few studies have experimentally explored the evolution of parasite virulence in the presence of defensive symbionts (King et al 2016;Ford et al 2017;G. May et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, few studies have experimentally explored the evolution of parasite virulence in the presence of defensive symbionts ( King et al, 2016 ; Ford et al, 2017 ; G. May et al, 2022 ). May et al (2022) have shown that when a plant host ( Zea mays ) is infected by a pathogenic fungus ( Ustilago maydis ), parasite fitness is maximized at higher levels of virulence in the presence of a defensive symbiont ( Fusarium verticillioides ), in agreement with our model.…”
Section: Discussionmentioning
confidence: 99%